2020
DOI: 10.1007/s40472-020-00283-1
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Landscapes in DCD Liver Transplantation

Abstract: Purpose of Review The transplant community continues to look for ways to help address the discordance between donor liver graft availability and patients on the liver transplant waiting list. Donation after circulatory death (DCD) donor livers represents one potential means to help address this discordance. The present review describes the changing landscape of DCD liver transplantation (LT). Recent Findings The number of DCD LTs performed annually within the USA has continued to grow on an annual basis. Impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 68 publications
(99 reference statements)
1
54
1
Order By: Relevance
“…We also demonstrate occlusion of the portal tract capillaries (Figure 1ii) which supply bile ducts (arrows). This is a key observation as cholangiocytes are known to be extremely sensitive to ischemia, 4 with ischemic‐type biliary lesions (ITBL) referred to as the Achilles’ heel of liver transplantation 5 . It was hoped that NMP would remove this major hurdle; however, the recent large OrganOx trial showed no benefit of liver NMP on rate of biliary strictures or ischemic cholangiopathy; the portal tract vascular occlusions which we demonstrate (Figure 1ii) could be one potential barrier preventing NMP from ameliorating cholangiocyte ischemia.…”
Section: Figurementioning
confidence: 99%
“…We also demonstrate occlusion of the portal tract capillaries (Figure 1ii) which supply bile ducts (arrows). This is a key observation as cholangiocytes are known to be extremely sensitive to ischemia, 4 with ischemic‐type biliary lesions (ITBL) referred to as the Achilles’ heel of liver transplantation 5 . It was hoped that NMP would remove this major hurdle; however, the recent large OrganOx trial showed no benefit of liver NMP on rate of biliary strictures or ischemic cholangiopathy; the portal tract vascular occlusions which we demonstrate (Figure 1ii) could be one potential barrier preventing NMP from ameliorating cholangiocyte ischemia.…”
Section: Figurementioning
confidence: 99%
“…LT volumes after 2012, corresponding with increased understanding of appropriate donor and recipient selection for minimizing DCDassociated complications. 5 Since then, DCD graft and recipient outcomes have markedly improved in both US and international reports of more recent experiences. 19,20 The validity of the UK DCD Risk Score in a contemporary US cohort -in the context of maturing DCD LT practices and improving outcomes -has yet to be demonstrated.…”
Section: Recent Studies Have Reported Substantial Increases In Us Dcdmentioning
confidence: 99%
“…Recent studies have reported substantial increases in US DCD LT volumes after 2012, corresponding with increased understanding of appropriate donor and recipient selection for minimizing DCD‐associated complications 5 . Since then, DCD graft and recipient outcomes have markedly improved in both US and international reports of more recent experiences 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…DCD grafts were reported as one of the strongest adverse risk factors in two well‐known liver donor risk indices from the United States (US) and Europe [4,5]. These grafts are still not well utilized compared with DBD livers, accounting for less than 10% of LT in the US [6,7]. This is primarily attributed to the inherent risks associated with these organs, especially in the early post‐transplant period [8].…”
Section: Introductionmentioning
confidence: 99%